(untitled) (Research, Society and Development, 2019)
The purpose of this work is to describe the research proposal of use of cladding to produce an AISI type 1020 and titanium steel sandwich structure. This work was presented at the VI GPESE Workshop of the Exhaust Systems Research Group of the Federal University of Itajubá. A brief review was used to investigate the main components of the cladding process in the literature to obtain a sandwich-type composite (clad). It is expected that the properties of the sheet steel combined with the titanium powder, generate a material having a long cutting strand where the titanium is placed, and the surfaces both lower and upper, have good impact strength.